Effectiveness of Educational Practices in University Students' Knowledge about Sun Protection and Its Relation to Sunlight Exposure: An Exploratory Study in a Portuguese Higher Education Institution - Bárbara Roque Ferreira; João Simões; Maria Eduarda Ferreira (MDPI AG, 2020)
Nowadays, there is worldwide recognition that health and educational outcomes are inextricably linked. It is also recognized that health education comprises opportunities to improve health literacy, including the improvement of knowledge and the development of life skills to promote individual health. It is also known that the behavioral practices regarding sun exposure are an important risk factor for skin cancer. Research is needed in this area to understand the contribution of the "Education for Health" curricular unit to these issues. Our exploratory research sought to collect information about the knowledge and practices regarding sun exposure of a group of Portuguese university students who have already attended this curricular unit. The results indicate that the participants show that, notwithstanding that they have already attended this curricular unit, they do not have more literacy on skin health, do not perceive that sun exposure habits are related to skin health and do not perceive that photoprotection constitutes prevention of skin cancer. The results support the need to promote the necessary reflection and debate on the way in which health education should be taught, as well as what is taught, in order to empower students to get decision-making skills associated with the adoption of healthier attitudes and practices, thus helping to prevent skin cancer.